Emerging Fast Food Culture in India: A Study of Select Advertisements (International Journal of Food and Nutritional Sciences, 2022)
Food is one most vital component of human life as it satisfies the basic biological need of hunger. Food habits of any culture are dependent on various factors. With the growth of human civilisation and society food has become a loaded term carrying social, cultural and political dimensions besides the biological one. With the rapid social changes the Indian food culture is also changing. Fast food has increased its value in Indian food habits. The advertisement industry has played a major role in the change of food culture. The present paper seeks to explore how the select advertisement of three famous food brands-Nestle’s Maggi, Dominos’ Pizza and McDonald’s Burger tries to influence the Indian audience through the use of Indian cultural elements. These advertisements were aired during 2022. These also reflect current Indian social realities.